Indeks Kigo pada Haiku Karya Matsuo Basho dalam Perspektif Semiotik Charles Sanders Peirce - Suri, Intan; Rahayu, Nana; Nuraisyah, Siti (Japanese Literature Study Program, Faculty of Letters, Dr. Soetomo University, 2023)
This research aims to describe the kigo index contained in Matsuo Basho's haiku from Charles Sanders Peirce's semiotic perspective. The method used in this research is descriptive qualitative with data collection techniques, namely literature study. The aim of this research is to find out what kigo indexes are in Matsuo Basho's haiku. The results of this research are that there are five haiku that explain kigo which has cause and effect. Kigo is related to natural conditions and seasons so it can be assumed that through kigo the poet's mood can be described. In this research, it is hoped that apart from being able to increase insight into indices, this research can become a reference for further research that wants to discuss kigo in haiku. Especially Matsuo Basho's haiku. Keywords: haiku; index; kigo; Matsuo Basho.